YPEL2 regulates the efficacy of BRD4-EZH2 dual targeting in EZH2Y641mut germinal center-derived lymphoma - Aránzazu Chamorro-Jorganes; Núria Profitós-Pelejà; Clara Recasens-Zorzo; Juan G Valero; Diana Reyes-Garau; Laura Magnano; Ray Butler; Antonio Postigo; Patricia Pérez-Galán; Marcelo Lima Ribeiro; Gaël Roué (Neoplasia: An International Journal for Oncology Research)
A significant proportion of diffuse large B cell lymphoma (DLBCL) and follicular lymphoma (FL) cases harbor a gain-of-function, heterozygous somatic mutation of the methyltransferase gene EZH2. While this factor is known to cooperate with the proto-oncogene MYC during malignant B cell development, the effect of interfering with both factors remains underexplored. Here we undertook the simultaneous evaluation of two epigenetic drugs targeting EZH2 methyltransferase activity and BRD4-mediated control of MYC transcription, CPI169 and CPI203, using preclinical models of DLBCL and FL with distinct EZH2 mutational status. We observed a specific and synergistic antiproliferative effect of these compounds in EZH2-mutated cells and mouse xenograft models, that was related to the abrogation of MYC transcriptional program and to tumor cell proliferation blockade at the G1 cell cycle phase. Gene expression profile, exploratory data analysis, and siRNA screening identified the PI3K/AKT-regulated gene and mitosis regulator, YPEL2, as a crucial factor involved in the efficacy of MYC/EZH2 dual targeting both in vitro and in vivo. Altogether, our results provide first pre-clinical evidence that simultaneous targeting of MYC and EZH2 is a safe and efficient approach that can be monitored by specific biomarkers, in aggressive lymphoid tumors of germinal center origin.